IL-27 Derived From Macrophages Facilitates IL-15 Production and T Cell Maintenance Following Allergic Hypersensitivity Responses - Suwanpradid, Jutamas; Lee, Min Jin; Hoang, Peter; Kwock, Jeffery; Floyd, Lauren P.; Smith, Jeffrey S.; Yin, Zhinan; Atwater, Amber R.; Rajagopal, Sudarshan; Kedl, Ross M.; Corcoran, David L.; Zhang, Jennifer Y.; et al. (Frontiers in Immunology, 2021)
Crosstalk between T cells, dendritic cells, and macrophages in temporal leukocyte clusters within barrier tissues provides a new concept for T cell activation in the skin. Activated T cells from these leukocyte clusters play critical roles in the efferent phase of allergic contact hypersensitivity (CHS). However, the cytokines driving maintenance and survival of pathogenic T cells during and following CHS remain mostly unknown. Upon epicutaneous allergen challenge, we here report that macrophages produce IL-27 which then induces IL-15 production from epidermal keratinocytes and dermal myeloid cells within leukocyte clusters. In agreement with the known role of IL-15 as a T cell survival factor and growth cytokine, this signaling axis enhances BCL2 and survival of skin T cells. Genetic depletion or pharmacological blockade of IL-27 in CHS mice leads to abrogated epidermal IL-15 production resulting in a decrease in BCL2 expression in T cells and a decline in dermal CD8+ T cells and T cell cluster numbers. These findings suggest that the IL-27 pathway is an important cytokine for regulating cutaneous T cell immunity.